Network disruption detected in NZ (New Zealand) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in New Zealand. Data sourced from IODA.
Network Disruption Incident ID: NZ-2026-0001. Severity: critical. Confidence: 70%